DISRUPTIVE TECHNOLOGY: FOUNDATIONS OF HUMAN RESOURCE TRANSFORMATION AND ITS IMPACT ON TECHNOPRENEURSHIP PRACTICES - Sulaeman, Moh. Muklis; Wibowo, Sandi Nasrudin (PT. LITERASI SAINS NUSANTARA, 2024)
The background of this research is based on the significant phenomenon in the current digital era where technology has become a major driver of change in various aspects of life, including the business world and entrepreneurship. Disruptive technology, defined as technology that disrupts existing business models, has fundamentally changed the business landscape. The aim of this research is to examine how disruptive technology affects the transformation of human resources and its impact on technopreneurship practices. This research method involves a qualitative literature review using data sources from Google Scholar spanning from 2019 to 2023. The results of the study indicate that in the rapidly evolving technological era, the presence of disruptive technology has become a major driver in the transformation of human resources and technopreneurship practices. Disruptive technology fundamentally alters the way we work, interact, and create value in society. This transformation includes changes in workforce needs and how entrepreneurs leverage innovation to create value.